An Ionization-Driven Air Plasma Jet - Jin, Shaohui; Nie, Lanlan; Zhou, Rusen; Luo, Jingyi; Lu, Xinpei (Frontiers in Physics, 2022)
Non-thermal atmospheric pressure plasma jets (NAPPJs) using ambient air as the inducer are of particular and desirable interest but with significant challenge. In this study, we report an air APPJ driven by ionization in the afterglow region, resembling the noble gas APPJs. A pin-to-nozzle electrode is used for the air plasma jet with a nanosecond pulsed DC high voltage as the power supply. Results show that the nozzle diameter plays an essential role in forming the air plasma jet. When the nozzle diameter is 3 mm, the air APPJ is driven by ionization in the afterglow region which is proved by the following three phenomena. Firstly, with an exposure time of 0.1 s, an obvious shiny line (the narrow channel plasma) formed by electron accumulation is observed in the jet. The narrow channel becomes much brighter with a grounding pin approaching the nozzle vertically. In comparison, there is no such phenomenon with a 1 mm diameter nozzle. Secondly, the afterglow region discharge current of the ionization-driven processes is hundreds of mA, distinguished from airflow-driven processes, the afterglow region current of which is typically zero. By using E-FISH to measure electric field in the afterglow region, it can detect electric field which has a maximum value of 10.5 kV/cm. Thirdly, the intensity of N2+ band is much stronger with a 3 mm diameter nozzle than it with a 1 mm diameter nozzle, indicating that the local electric field plays important role in the discharge. We expect this study can offer useful guidelines on the design and understanding of the ionization-driven air plasma jets.